2021
DOI: 10.1186/s12896-021-00683-w
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes for mRNA delivery: a novel biotherapeutic strategy with hurdles and hope

Abstract: Over the past decade, therapeutic messenger RNAs (mRNAs) have emerged as a highly promising new class of drugs for protein replacement therapies. Due to the recent developments, the incorporation of modified nucleotides in synthetic mRNAs can lead to maximizing protein expression and reducing adverse immunogenicity. Despite these stunning improvements, mRNA therapy is limited by the need for the development of safe and efficient carriers to protect the mRNA integrity for in vivo applications. Recently, leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 110 publications
1
43
0
Order By: Relevance
“…In a recent study, an EV-based antibody array profiling identified CD151, CD171, and Tetraspanin 8 among the most significant molecules to differentiate histological lung cancer patients from cancer-free individuals [8]. EVs are also considered a potential therapeutic resource as a drug cell delivery vector based on their efficient cellular uptake [6,7,9,10], as recently illustrated by intravenous administration of engineered EVs loaded with curcumin able to target an ischemic brain lesion in rodents [11].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, an EV-based antibody array profiling identified CD151, CD171, and Tetraspanin 8 among the most significant molecules to differentiate histological lung cancer patients from cancer-free individuals [8]. EVs are also considered a potential therapeutic resource as a drug cell delivery vector based on their efficient cellular uptake [6,7,9,10], as recently illustrated by intravenous administration of engineered EVs loaded with curcumin able to target an ischemic brain lesion in rodents [11].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, when looking at the forefront of VNs-mediated drug delivery, we can witness the increasing relevance of cell-based VNs such as exosomes [ 59 ] or outer membrane vesicles (OMVs) from Gram-negative bacteria [ 60 ], whose major hallmark is their expectedly high biocompatibility and low immunogenicity. Exosomes are extracellular vesicles that integrate proteins and nucleic acids of their secreting cells, and which can affect function and properties of other cells able to internalize them [ 59 ]; as such, recent efforts address their engineering for targeted drug delivery [ 61 , 62 ], also for diverse dermatological applications [ 63 , 64 , 65 ] and wound healing [ 66 ]. Besides exosomes, OMVs are also becoming prominent actors in several biomedical applications, including recent examples where engineered OMVs from transgenic Escherichia coli have been used for DTD of biopharmaceuticals, alone [ 60 ] or in combination with phototherapy [ 67 ].…”
Section: Overview Of Current Methods For Dermal and Transdermal Drug Deliverymentioning
confidence: 99%
“…Another promising delivery tool for therapeutic mRNAs could be exosomal delivery [ 177 , 178 ]. Given that exosomes play a pivotal role in mRNA transfer between cells and have membrane permeability properties, they could be an optimal delivery system for mRNAs.…”
Section: Formulation Strategiesmentioning
confidence: 99%